Use of digital resources to expand l2 vocabulary at Centro Educativo Comunitario Intercultural Bilingüe Patricio Espinoza Bermeo - Pupiales Pupiales, Erika Janeth (2025)
To analyze the role of digital resources in enabling vocabulary acquisition in students at the Institution.